A case study of the application of adaptive reuse on an ancestral home turned into a restaurant in Metro Manila - Casuga, Naomi Grace V.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This case study focused on how adaptive reuse was applied on an ancestral house turned into a restaurant in Metro Manila by describing the current interior design of the main dining area and by determining the preserved elements in the restaurant. Using theoretical sampling, My Mothers Garden, located in Pasay City and owned and designed by Archt. Pablo Antonio in 1948, was identified. The study analyzed the changes made in the main dining area based on how the current owner, Ms. Malu Antonio-Veloso, understood and perceived the concept of adaptive reuse. Site observation, photo documentation, and area measurement were done to describe the interior design of the main dining area of the restaurant. An interview using an open-ended questionnaire was conducted with Ms. Veloso to obtain her insights on the decisions she implemented on the reuse of the structure as a restaurant. The method of conservation done was then analyzed in alignment with the basic conservation principles of the National Historical Commission of the Philippines (NHCP) and the different perspectives on the theory of adaptive reuse. The results showed that there were no problems encountered on the preservation of the structure because the ancestral house was designed for longevity. The intrinsic ability of the interior to easily host new functions and users also contributed to this successful implementation. To ensure its continued sustainability, constant inspection and maintenance of the building is needed. Furthermore, because the authenticity of the house was maintained, the structure is currently under review towards its declaration as a heritage house. This suggested that post-colonial modern houses are already considered as heritage houses and need to be conserved. In conclusion, the preservation and application of adaptive reuse on My Mothers Garden was deemed effective due to its initial design, but its success and sustainability rely heavily on the involvement and decisions of the owner.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Buildings -- Remodeling for other use -- Case studies; Dwellings -- Remodeling -- Philippines -- Pasay City